Design and implementation of voltage regulator for a power supply - Thee, Wai Ken (2017)
The conventional use of voltage regulator has been widely introduced in the electronic appliances. With the advancement of technology and complexity of circuit designs, the implementation of voltage regulator has become necessary to maintain a constant desired output voltage and regulate the unregulated input voltage from the power supply. This report displays the objective to design and implementation of several types of voltage regulators for a power supply. The two most commonly used voltage regulator types, namely linear regulator and switching regulator has been researched, simulated, designed and recorded in this report. The types of linear regulator designed in this project are simple series voltage regulator, simple shunt voltage regulator, fixed regulator and variable regulator. This project also includes the implementation of switching regulators such as buck converter, boost converter and inverting converter through the utilization of MC33063A microchip. These voltage regulators have been simulated by using MULTISIM and PSIM. The results of simulation, calculation and measurements are included in the report and actual circuits have been designed to display the results in contrast to simulation results.